PENGARUH FEE BASED INCOME DAN TRANSAKSI E-BANKING TERHADAP PERUBAHAN LABA BANK BUMN - Nolis Asiska; Permata Dian Pratiwi (Universitas Ahmad Dahlan, 2022)
E-banking technology provides conveniences and speed to help customers in using financial services. The bank should increase the number of E-Banking customers to generate more fee-based Income. Thus the bank income will be increased. This study aims to determine the effect of Fee-Based Income and E-Banking Transactions on Profit Changes in state-owned banks listed on the Indonesia Stock Exchange from 2011-to 2020. The population of this research is four state-owned banking companies listed on the Indonesia Stock Exchange for the period 2011-2020. This research used 39 observations as samples, later decreasing to 31 observations due to abnormal data healing outlier detection. The results of this study show that 1). Fee-Based Income has a significant positive effect on profit changes, 2). E-Banking transaction has no significant effect on Profit Change at state-owned banks listed on the Indonesia Stock Exchange for the 2011-2020 period.